Development Review of Research about Motivation on Employee Performance Topics over The Past Ten Years in Online Journals - Indah Wulansari; Humaira Uswatun Hasanah; Jacqueline Lewaney; Tiarapuspa Tiarapuspa (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
In an organization, motivation is the very important thing that it cannot be separated from employee performance. To get good performance, it is necessary to improve employee work motivation. Most employees need motivation to feel good about their jobs and perform optimally. Some employees are financially motivated while others find recognition and rewards personally motivating. A good leader will certainly create a comfortable environment and motivate employees with the aim that the enthusiasm for work and providing maximum performance. Work motivation is an important factor for obtaining good performance. This study aims to be a reference for researchers who plan to make research with the theme of motivation on employee performance so that researchers have a plan about what cases have been studied by previous researchers and then provide ideas for further development. The data in this study were taken from 30 articles over the past 10 years with the theme of motivation on employee performance and published in the Trijurnal Online Research Institute of Trisakti University and Emerald Insight Journals.